2021
DOI: 10.1159/000513961
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Predictive Markers for Recurrence of Esophageal Cancer after Esophagectomy

Abstract: Introduction: We studied whether perioperative nutritional, immunological factors or postoperative inflammatory responses predicted esophageal cancer (EC) progression and prognosis in patients who received esophagectomies. Methods: We evaluated preoperative prognostic nutritional index (PNI), BMI, neutrophil-to-lymphocyte ratio (NLR), intraoperative blood loss, postoperative C-reactive protein (CRP) max, recurrence-free survival (RFS), and overall survival (OS) in 111 patients with pStage I–IV squamous cell EC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Inflammatory and nutritional status is closely associated with carcinogenesis, cancer growth and progression ( 8 , 9 ). Moreover, prognostic values of several preoperative inflammatory and nutritional indicators have been explored in ESCC patients in the past few years ( 13 , 14 , 16 ). A meta-analysis conducted by Ishibashi et al ( 13 ) aimed to explore the correlations between PLT associated markers and overall survival (OS) in ESCC.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Inflammatory and nutritional status is closely associated with carcinogenesis, cancer growth and progression ( 8 , 9 ). Moreover, prognostic values of several preoperative inflammatory and nutritional indicators have been explored in ESCC patients in the past few years ( 13 , 14 , 16 ). A meta-analysis conducted by Ishibashi et al ( 13 ) aimed to explore the correlations between PLT associated markers and overall survival (OS) in ESCC.…”
Section: Discussionmentioning
confidence: 99%
“…Based on 14 retrospective studies, they demonstrated that low PLR level was significantly associated with well OS. Fujiwara et al ( 14 ) analyzed several indexes based on inflammation and nutrition in 111 ESCC patients and the results revealed low PNI was associated with shorter recurrence-free survival (RFS). Geng et al ( 16 ) revealed that SIRI was significantly related to OS and served as an independent prognostic score in 916 ESCC patients with radical resection.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations